Evaluation of coupling coordination relationship between different habitat materials and vegetation system in the engineering disturbed area - Zhao, Bingqin; Shen, Yuanyang; Hu, Xinkai; Wu, Yuhang; Zhang, Lun; Xia, Dong; Xu, Wennian; Gao, Ruzhang (Frontiers in Materials, 2022)
In order to explore the coupling coordination relationship between habitat materials and vegetation system in the engineering disturbed area, six different vegetation restoration patterns in Xiangjiaba engineering disturbed region were utilized as research objects. An evaluation system of 14 habitat materials indicators and 10 vegetation indicators was established. The weight of each indicator was determined by Principal Component Analysis (PCA), and the interrelationship between habitat material and vegetation system was investigated using the Partial Least Square Path model (PLS-PM). Finally, a model for the degree of coupling coordination between habitat materials and vegetation system under different vegetation restoration modes was constructed. The results showed that: 1) habitat materials and vegetation system are closely related, and the habitat materials have a stronger impact on ecosystem restoration. Artificial vegetation restoration technologies can effectively improve soil conditions in engineering disturbed areas, allowing for vegetation restoration in a healthy environment. 2) Under different vegetation restoration patterns, the habitat materials and vegetation coupling coordination index of natural forest plots, frame beam filling soil plots, thick layer base material spraying plots, guest external soil spray seeding plots, vegetation concrete plots, and abandon slag slope plots was 0.767, 0.673, 0.669, 0.625, 0.557, and 0.400, respectively. The development of habitat materials and vegetation in guest external soil spray seeding plots was of a synchronous type. The vegetation development lagged behind habitat materials in thick layer base material spraying plots, vegetation concrete plots, and abandon slag slope plots, while habitat materials lagged behind vegetation development in natural forest plots, frame beam filling soil plots. The model for the degree of coupling coordination between habitat materials and vegetation constructed in this study can serve as a scientific reference for evaluating the impact of ecological restoration engineering in other similar projects.